Penerapan Metode Non Directive Dengan Menggunakan Peta Untuk Meningkatkan Aktivitas dan Hasil Belajar Bahasa Inggris Siswa di Kelas VIII SMP - Ahmad Bakhtiar; Irfan Hadi; Nia Liska Saputri; Zeinora Zeinora; Nana Suyana (Jurnal Ilmiah Wahana Pendidikan, 2022)
The aims of this study were: (1) Class VIII-1 students' learning activities at SMP Negeri 10 Depok in applying the Non-Directive Method using Map Media. (2) student learning outcomes of class VIIII in applying the non-directive method using map media. The subjects in this study were 38 class VIII-1 students of SMP Negeri 10 Depok. Data collection techniques used direct and indirect communication, the data collection tool in this study used observation and test sheets. The tests used are in accordance with the achieved curriculum objectives and are taken from textbooks for class VIII SMP Negeri 10 Depok. To collect research data using worksheets and post tests. This research was conducted in 2 cycles, namely cycle I and cycle II. Each cycle has stages - the stages of planning, implementation, observation and reflection. The results of this study indicate that there is an increase in students' learning abilities with student mastery reaching 35.18% then increasing in cycle I to 46.22%. From the results of the research, it can be seen also the increase in students' learning abilities with worksheets in cycles. 1. the level of student completeness reached 69.44% then increased in cycle II to 94.44%. From the analysis carried out, it can be concluded that the non-directive learning method can increase student learning activities and outcomes in SMP Negeri 10 Depok students in the 2010/2011 academic year. Indonesia,